(untitled) (Proceedings of the Society of Antiquaries of Scotland, 2000)
Between 1980 and 1984 a number of finds of EBA metalwork were recovered via metal-detecting from an area of rough ground at the head of a small disused quarry. This report considers the character of the metalwork and the context in which that material was deposited. It concludes that the entire assemblage could have resulted from more than one period of votive deposition, and that these activities focused upon a prominent, but natural, long mound and occurred in an area which may have been demarcated by other natural points of reference.